Developing problem-based learning student worksheet on matrix materials to improve students’ critical thinking skills - Nurnugroho, Burhanudin Arif; Khoirunisa, Zahro (Bulletin of Applied Mathematics and Mathematics Education, 2024)
This research was conducted based on problems at MAS Taruna Al Quran Yogyakarta, that the mathematics learning still relied on a publisher generated sources which only focused on students’ understanding, but not yet targeted their middle-low critical thinking skills. It then aims to develop a problem-based learning worksheet on matrix material, which can improve students' critical thinking skills, especially on interpretation and inference indicators. The research used ADDIE development model which has five stages, including analysis, design, development, implementation, and evaluation. Finally, it successfully developed the worksheet rich of learning activities stimulating the students’ critical thinking through the syntax of problem-based learning. The media expert assessment scored 46/50 (very good) and the content expert assessment scored 100/105 (very good). The worksheet also considered practical for use, as shown by the average results of participant questionnaire response scored 84.4 (very good) in the small-scale test and scored 90.5 (very good) in the large-scale test. The developed worksheet also created a significant influence in improving the students’ critical thinking skills by an increase of 25.3%.